PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN FINANCING TO DEPOSITO RATIO (FDR) TERHADAP PROFITABILITAS DENGAN NON PERFORMING FINANCING (NPF) SEBAGAI VARIABEL INTERVENING PADA BANK UMUM SYARIAH - Ahmad Hakimul 'Izza; Budi Utomo (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This study examined the effect of capital adequacy ratio (CAR) and financing to deposit ratio (FDR) on profitability with non performing financing (NPF) as intervening variables in Islamic commercial banks for the period 2016-2020. The results of this study show that the capital adequacy ratio has a positive effect on profitability (ROA), but in contrast to financing to deposit ratio (FDR) which has no effect on profitability (ROA), then non performing financing (NPF) has a positive effect on profitability (ROA). The study also found that non performing financing (NPF) does not mediate the relationship between capital adequacy ration (CAR) to profitability (ROA), but non performing financing (NPF) is proven to mediate the relationship between financing to deposit ratio (FDR) to profitability (ROA).